Boarding control system for improved accessibility to offshore wind turbines: Full-scale testing. (December 2015) - Auestad, Øyvind F.; Gravdahl, Jan T.; Perez, Tristan; Sørensen, Asgeir J.; Espeland, Trygve H.
Abstract: This paper considers the dynamic modelling and motion control of a Surface Effect Ship (SES) for safer transfer of personnel and equipment from vessel to-and-from an offshore wind-turbine. The control system designed is referred to as Boarding Control System (BCS). The performance of this system is investigated for a specific wind-farm service vessel—The Wave Craft. On a SES, the pressurized air cushion supports the majority of the weight of the vessel. The control problem considered relates to the actuation of the pressure such that wave-induced vessel motions are minimized. Results are given through simulation, model- and full-scale experimental testing. Abstract : Highlights: Modelling and control of a Surface Effect Ship. The automatic control system ensures that one can access offshore wind turbines in higher sea states then without it. Mathematical modelling of a hinged ship to an offshore structure. Simulation and model test results.